COGNITIVE – PRAGMATIC FEATURES OF PROVERBS WITH THE “PARENTS” MEANING - Khayitova Shohida Erkin Qizi, (Лучшие интеллектуальные исследования, 2024)
The present article offers a state-of-the-art cognitive-pragmatic view of proverbs by reviewing “Parents” meaning.